Pengaruh Kewajiban Kepemilikan NPWP Dan Penagihan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Sanksi Perpajakan Sebagai Variabel Moderasi - Riantini, Kirana; Sanulika, Aris (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to examine the effect of the obligation to own a NPWP and collect taxpayers on individual taxpayer compliance. In addition, this study also examines the role of supporting variables related to the moderation of tax sanctions. This type of research is associative quantitative research using random sampling technique. The research sample population was 100 respondents who were registered at KPP Pratama Kebayoran Baru Dua with the help of the SPSS 25 program. The research methodology used was Descriptive Statistical Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), Hypothesis Test (Test Multiple Linear Regression, Moderated Regression Analysis Test, Coefficient of Determination Test, Partial Test, Model Fit Test). Based on the test results of this study, it shows that the obligation to own a NPWP has an effect on individual taxpayer compliance and taxpayer collection has an effect on individual taxpayer compliance. This study also shows that tax sanctions strengthen the influence of the obligation to own a NPWP on individual taxpayer compliance and tax sanctions strengthen the effect of taxpayer collection on individual taxpayer compliance.